Nablus Public Library - Asfour, Ahmad; Shihab, AlGhalee; Bishawi, Islam; Najjar, Yasmeen (My University, 2021)
Public libraries are one of the most missing facilities in Nablus. It is one of the most important places to spread culture and awareness among citizens. Therefore, a public library project was chosen as a graduation project. In this graduation project, five main parts has been studied: architectural, structural, environmental and economical parts. As for the architectural aspect, the architectural requirements have been conducted for the library in terms of function and environmental requirements and it has been compared with the existing architectural design. This includes site analysis for the proposed site and a case study for a public library that satisfies these architectural requirements. After that a modification of the architectural design based on the obtained data has been prepared. In the structural part, the structural system has been chosen based on the different types of lateral and gravity loads that is facing the building, and a full-detailed design for the structural elements has been conducted as well. Environmental studies are also included in this project, it includes the daylight factor calculations for different spaces and also an environmental analysis for the site. Finally, a quantity surveying and cost estimation for the project has been performed based on the modifications conducted in the project and the proposed materials for each element.